Cost-Effectiveness Analysis of Capecitabine Plus Oxaliplatin Versus Gemcitabine Plus Oxaliplatin as First-Line Therapy for Advanced Biliary Tract Cancers - Chen, Ruijia; Zhang, Yalan; Lin, Kongying; Huang, Defu; You, MaoJin; Lai, Yanjin; Wang, Jinye; Hu, Yingying; Li, Na (Frontiers in Pharmacology, 2022)
Background: In the first-line treatment of BTCs, XELOX showed comparable clinical efficacy and safety to GEMOX, with fewer visits and better treatment management. Our study aims to investigate the cost-effectiveness of XELOX and GEMOX as the first-line therapy for BTCs from the perspective of the Chinese healthcare systems and to provide valuable suggestions for clinical decision-making. Methods: A Markov model was developed using the Phase 3 randomized clinical trial (ClinicalTrials.gov number, NCT01470443) to evaluate the cost-effectiveness of XELOX and GEMOX. Quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICERs) were used as the primary outcomes of the model. Uncertainty was assessed using univariate and probabilistic sensitivity analysis. Results: The QALYs for the XELOX and GEMOX groups were 0.66 and 0.54, respectively. In China, the total cost of XELOX treatment is $12,275.51, which is lower than the GEMOX regimen and more effective, making it the preferred regimen. Sensitivity analysis determined that XELOX therapy has a stable economic advantage in China. Conclusions: Compared to GEMOX, XELOX is a more cost-effective treatment as a first-line treatment for advanced BTC from the perspective of the Chinese health service system. Conclusions: XELOX, compared with GEMOX, is a more cost-effective treatment as the first-line treatment for advanced BTCs from the perspective of the United States and China’s health service system.